Pascal / An Introduction to Methodical Programming - Findlay William; Watt David A (Pitman Publishing, 1985)
Preface, First Steps in Programming, Further Simple Data Types, Arrays and Strings, Subprograms, Further Data Structures, Additional Topics, Appendices, Index.